2006
DOI: 10.1111/j.1365-2966.2006.10894.x
|View full text |Cite
|
Sign up to set email alerts
|

The luminosity, colour and morphology dependence of galaxy filaments in the Sloan Digital Sky Survey Data Release Four

Abstract: We have tested for luminosity, colour and morphology dependence of the degree of filamentarity in seven nearly two‐dimensional strips from the Sloan Digital Sky Survey Data Release Four (SDSS DR4). The analysis was carried out at various levels of coarse graining allowing us to address different length‐scales. We find that the brighter galaxies have a less filamentary distribution than the fainter ones at all levels of coarse graining. The distribution of red galaxies and ellipticals shows a higher degree of f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 102 publications
(110 reference statements)
3
52
0
Order By: Relevance
“…The Universe's main matter (dark matter) follows a hierarchical model of structure formation and evolution (Kaiser 1986;White & Frenk 1991) depicted in great detail with numerical simulations, which trace the gravitational growth of dark matter haloes (Evrard et al 2002;Springel et al 2005;Dolag et al 2006). The so-called cosmic web filling the present Universe has been observationally confirmed by several large spectroscopic surveys (Colless et al 2001;Pimbblet et al 2004;Pandey & Bharadwaj 2006), revealing the presence of large-scale filaments that feed nodes of massive and rich galaxy clusters (e.g. Jauzac et al 2012).…”
Section: Introductionmentioning
confidence: 88%
“…The Universe's main matter (dark matter) follows a hierarchical model of structure formation and evolution (Kaiser 1986;White & Frenk 1991) depicted in great detail with numerical simulations, which trace the gravitational growth of dark matter haloes (Evrard et al 2002;Springel et al 2005;Dolag et al 2006). The so-called cosmic web filling the present Universe has been observationally confirmed by several large spectroscopic surveys (Colless et al 2001;Pimbblet et al 2004;Pandey & Bharadwaj 2006), revealing the presence of large-scale filaments that feed nodes of massive and rich galaxy clusters (e.g. Jauzac et al 2012).…”
Section: Introductionmentioning
confidence: 88%
“…Systems of galaxies determined in the SDSS have been studied by a number of authors (Pandey & Bharadwaj 2005;Gott et al 2005;Park et al 2005;Pandey & Bharadwaj 2006;Gott et al 2008;Pandey & Bharadwaj 2008;Kitaura et al 2009;Choi et al 2010;Sousbie et al 2011;Einasto et al 2011b,a;Sheth & Diaferio 2011;Pimbblet et al 2011;Platen et al 2011). The overall shapes of superclusters have been described by the shape parameters or approximated by triaxial ellipses (Jaaniste et al 1998;Basilakos et al 2001;Kolokotronis et al 2002;Basilakos 2003;Einasto et al 2007aEinasto et al , 2011bCosta-Duarte et al 2011;Luparello et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Trujillo et al (2006) also showed by analyzing recent observational data from large galaxy surveys that the spin axes of void galaxies tend to be inclined to the void surfaces, retaining an initial memory of tidally induced alignment. Pandey & Bharadwaj (2006) have shown that galaxy luminosity and color depend on the filamentarity of the large-scale environment. More recently, they also presented the result that the star formation rates of galaxies are correlated with the filamentarity of the surrounding large-scale structure (Pandey & Bharadwaj 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Pandey & Bharadwaj (2006) have shown that galaxy luminosity and color depend on the filamentarity of the large-scale environment. More recently, they also presented the result that the star formation rates of galaxies are correlated with the filamentarity of the surrounding large-scale structure (Pandey & Bharadwaj 2008). Hernandez et al (2007) found a one-to-one correspondence between the value of the galaxy spin parameter and morphological type, while Hernandez & Cervantes-Sodi (2006) and Cervantes-Sodi & Hernandez (2008) have noted that the spin parameters of observed galaxies are strongly correlated with their color and chemical abundance.…”
Section: Introductionmentioning
confidence: 99%